Research student supervision : an approach to good supervisory practice. - Zainal Abiddin, Norhasni; Hassan, Aminuddin; Ahmad, Abdul Razaq (Bentham Science Publishers, 2009)
Good supervisory practices help students fulfill their potential and contribute to the University’s research profile. At many universities, the terms of a supervisory relationship are left almost entirely to the discretion of individual research students and supervisors. While this approach usually works well, it occasionally proves unsatisfactory. A lack of clarity between student and supervisor with regard to expectations and responsibilities can adversely affect progress towards the completion of the degree. This article reviews the literature on research/graduate student supervision. It describes best practices in research student supervision, and setd out the rights and responsibilities of both students and their supervisors. It is intended to provide some useful guidelines for research students and supervisors in a critically important part of graduate education: the supervision of students’ thesis writing and research. Therefore, a review of literature concerning research student supervision is hoped to assist all participants in the supervisory process to articulate their expectations clearly, and thereby to reduce potential problems and to facilitate the creative process of thesis preparation.